Gastropod in The Intertidal Zone Tiwoho and Tongkaina, North Sulawesi - Budi A.R.D. Juliantoro; Erly Y. Kaligis; Natali D.C. Kumampuk; Kurniati Kemer; Carolus P. Paruntu; Medy Ompi (JURNAL PESISIR DAN LAUT TROPIS, 2025)
This study aimed to identify the species, measure species density, and assess the diversity, similarity, and dominance of gastropod communities in the intertidal zones of Tiwoho and Tongkaina. The belt transect method was used. A measuring tape was stretched for 30 meters along the lowest tide line, with a 1-meter width on each side (total width of 2 meters), running parallel to the shoreline. The distance between each transect was 5 meters, and three transects were set up at each site.  Gastropods were collected within the 30 × 2 meter transect area. Before collection, photographs of each gastropod still attached to the substrate were taken. Each sample was then placed in a labelled plastic bag according to its transect number. Samples were stored in a deep freezer in the laboratory before identification and measurement of their length and width. Identification was done to the lowest possible taxonomic level (genus or species) using identification guides. The results showed that 14 gastropod species were found at the Tiwoho site and 11 species at the Tongkaina site. The most abundant species at Tiwoho was Drupina grossularia, while Engina alveolata and Clivipollia incarnata were the most common at the Tongkaina. Both sites showed moderate diversity and high evenness, indicating a stable gastropod community. There were no dominant species at either site. Environmental conditions at both locations were considered suitable for gastropod habitation Keywords: Gastropod, Tiwoho, Tongkaina, belt transect, litoral zone   Abstrak Penelitian ini bertujuan untuk mengetahui jenis, kepadatan, keanekaragaman, kesamaan, dan dominasi gastropoda di zona intertidal Tiwoho dan Tongkaina. Metode yang digunakan adalah belt transect dengan panjang 30 meter dan lebar efektif 2 meter (1 meter ke kiri dan kanan garis utama), diletakkan di batas surut terendah sejajar garis pantai. Jarak antar transek adalah 5 meter dengan tiga kali ulangan di setiap lokasi. Sampel gastropoda dikumpulkan sepanjang transek (30 × 2 m), difoto saat masih menempel di substrat, kemudian dimasukkan ke dalam plastik berlabel nomor transek. Sampel disimpan dalam deep freezer sebelum dilakukan identifikasi hingga tingkat genus atau spesies di laboratorium, serta dilakukan pengukuran panjang dan lebar menggunakan buku identifikasi sebagai panduan. Hasil penelitian menunjukkan bahwa terdapat 14 spesies gastropoda di stasiun Tiwoho dan 11 spesies di stasiun Tongkaina. Spesies dengan kepadatan tertinggi di Tiwoho adalah Drupina grosullaria, sedangkan di Tongkaina adalah Engina alveolata dan Clivipollia incarta. Keanekaragaman tergolong sedang, keseragaman populasi tinggi, dan tidak ditemukan spesies yang mendominasi di kedua lokasi. Parameter lingkungan di kedua stasiun mendukung kelangsungan hidup gastropoda. Kata kunci: Gastropoda, Tiwoho, Tongkaina, belt transect, zona litoral